CVD – Composites as Perspective Materials for Interference Optics of an IR Spectrum Range (Review) - Zinchenko, V.F.; Chygrynov, V.E.; Timukhin, Ie.V. (Physics and Chemistry of Solid State, 2015)
The general mechanism of thermal evaporation in vacuum of chalcogenide (oxide) metal − germanium composites is established. Thermodynamic calculations define values of conditional temperatures which are essentially lower in comparison with such for initial components. Possibility of formation at condensation on a substrate of thin-film coatings which possess high optical and operational parameters is revealed.